Formation of the hotel business model based on the network management form - V. A. Zhukov; A. D. Chudnovskii (Вестник университета)
The competitive advantages, acquired by hotels using the network form of business organization, have been highlighted. Based on the analysis of the diverse opinions of specialists, the concept of a «hotel chain» has been clarified. Тhe difference between the concepts of «hotel chain» and «hotel brand» has been shown. The features of the formation of hotel chains in Russia have been emphasized. A management contract and its components, that require agreement between the hotel operator and the owner of an independent hotel, have been considered. The prospectivity for an independent hotel to conclude with a hotel operator of a franchise agreement with a view to joining the network has been shown. The data on the amount of franchisee contributions to franchisor from various hotel operators for certain hotel brands in 2018 have been presented.